Structural, Optical, Thermal, Morphological and Electrical Studies of PEMA/PMMA Blend Filled with CoCl2 and LiBr As Mixed Filler - Abdelrazek, E. M.; Asnag, G. M.; Oraby, A. H.; Abdelghany, A. M.; Alshehari, A. M.; Gumaan, Mohammed S. (Springer Nature, 2020)
Structural, optical, thermal, morphological and electrical features of pure blend and composites based on poly(ethyl methacralyte) (PEMA) and poly (methyl methacrylate) (PMMA) filled with different contents of cobalt chloride (CoCl2) and lithium bromide (LiBr) were investigated. The composite samples at various concentrations of mixed filler were prepared using the casting method. X-ray diffraction (XRD) showed an amorphous feature of the pure blend films. Fourier transform infrared (FT-IR) spectra depicted that components of the blend, PEMA and PMMA polymers, are miscible. Ultraviolet and visible (UV-Vis.) measurement revealed that the values of the optical energy gap are decreasing with increasing mixed filler concentrations. Scanning electron microscopy (SEM) after adding the mixed filler shows small granules and bright spots on the surface of the blend. Differential scanning calorimetry (DSC) results show that adding mixed filler to polymeric solution enhances their thermal stability. The plot of DC conductivity versus temperature shows the Arrhenius model (linear variation).